Toward an intuitive understanding of the structure of near-vector spaces. Issue 9 (2nd September 2022) - Howell, K.-T.; Marques, S.
Abstract: In this article we analyze the definition André proposed for near-vector spaces to make it more transparent. We also study the class of near-vector spaces over division rings and give a characterization of regularity that gives a new insight into the decomposition of near-vector spaces into regular subspaces. We explicitly describe span and deduce a new characterization of subspaces.